Estimating the magnitude of cancer overdiagnosis in Australia. Issue 4 (19th December 2019) - Glasziou, Paul P; Jones, Mark A; Pathirana, Thanya; Barratt, Alexandra L; Bell, Katy JL
Abstract: Objectives: To estimate the proportion of cancer diagnoses in Australia that might reasonably be attributed to overdiagnosis by comparing current and past lifetime risks of cancer. Design, setting, and participants: Routinely collected Australian Institute of Health and Welfare national data were analysed to estimate recent (2012) and historical (1982) lifetime risks (adjusted for competing risk of death and changes in risk factors) of diagnoses with five cancers: prostate, breast, renal, thyroid cancers, and melanoma. Main outcome measure: Difference in lifetime risks of cancer diagnosis between 1982 and 2012, interpreted as probable overdiagnosis. Results: For women, absolute lifetime risk increased by 3.4 percentage points for breast cancer (invasive cancers, 1.7 percentage points), 0.6 percentage point for renal cancer, 1.0 percentage point for thyroid cancer, and 5.1 percentage points for melanoma (invasive melanoma, 0.7 percentage point). An estimated 22% of breast cancers (invasive cancers, 13%), 58% of renal cancers, 73% of thyroid cancers, and 54% of melanomas (invasive melanoma, 15%) were overdiagnosed, or 18% of all cancer diagnoses (8% of invasive cancer diagnoses). For men, absolute lifetime risk increased by 8.2 percentage points for prostate cancer, 0.8 percentage point for renal cancer, 0.4 percentage point for thyroid cancer, and 8.0 percentage points for melanoma (invasive melanoma, 1.5 percentage points). An estimated 42% of prostate cancers, 42% of renal cancers, 73% of thyroid cancers, and 58% of melanomas (invasive melanomas, 22%) were overdiagnosed, or 24% of all cancer diagnoses (16% of invasive cancer diagnoses). Alternative assumptions slightly modified the estimates for overdiagnosis of breast cancer and melanoma. Conclusions: About 11 000 cancers in women and 18 000 in men may be overdiagnosed each year. Rates of overdiagnosis need to be reduced and health services should monitor emerging areas of overdiagnosis.